Implementation of National Insight Values in Successful Social Knowledge Learning Case Study: Elementary School Students - Musakirawati Musakirawati; Rahayu Ahsari; Abdul Basith Rahman; Abdul Tahir; Made Ayu Anggreni (Journal on Education, 2024)
Life in the nation and state requires constant discussion about the breadth of a scientific study of national insight in Indonesia. The principles of Pancasila serve as a link to foster national consciousness. With globalization, Indonesia's state ideology and Pancasila as the nation's way of life are losing their value and being replaced by foreign cultures. This article discusses how the benefits of social science learning to increase nationalistic insight in elementary school students. The focus of the research is the practical implementation of social science lessons in expanding the nationalistic insight of an elementary school student. The purpose of this research is to measure how well various educational approaches can improve students' understanding of progress. The research shows that teachers can implement nationalistic insights sourced from social science subjects through two approaches with Contextual Teaching Model (CTL) learning methods and also practical methods such as Indonesian history art performances, Indonesian history exhibitions and others. Effective learning can improve students' understanding of the development of Indonesian independence and strengthen students' nationalism.